2016
DOI: 10.1111/tmi.12678
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of non‐monetary incentives on facility delivery in rural Zambia: a clustered randomised controlled trial

Abstract: Abstractobjectives In Zambia, only 56% of rural women deliver in a health facility, and improving facility delivery rates is a priority of the Zambian government. 'Mama kit' incentives -small packages of childcare items provided to mothers conditional on delivering their baby in a facility -may encourage facility delivery. This study measured the impact and cost-effectiveness of a US$4 mama kit on rural facility delivery rates in Zambia.methods A clustered randomised controlled trial was used to measure the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…However, in that context the kits were provided at ANC visits, and thus kit uptake was tied to ANC attendance; the paper did not report effect on other health services. In a RCT in Zambia, provision of a mama kit containing diapers, a sheet and a blanket to women who deliver at health facilities increased facility-based delivery levels [19]. However, the fact that receipt of the kit was conditional on utilization renders this context very different from the trial analyzed here.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in that context the kits were provided at ANC visits, and thus kit uptake was tied to ANC attendance; the paper did not report effect on other health services. In a RCT in Zambia, provision of a mama kit containing diapers, a sheet and a blanket to women who deliver at health facilities increased facility-based delivery levels [19]. However, the fact that receipt of the kit was conditional on utilization renders this context very different from the trial analyzed here.…”
Section: Discussionmentioning
confidence: 96%
“…In general, there is limited evidence around the associations between safe birth kits and maternal health service use. However, one RCT conducted in Zambia reported that distribution of “mama kits” containing only a cloth, diapers and blanket to women delivering in a facility (and only these women) increased the rate of facility delivery [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies were conducted in East Africa (Kenya (n = 3) [20][21][22], Uganda (n = 2) [23,24] Tanzania (n = 2) [9,25], Eritrea (n = 1) [26], and Ethiopia (n = 1) [27]). Two were conducted in Southern Africa (Zambia (n = 1), [28], and Lesotho (n = 1) [29]), and one in West Africa (Mali) [30].…”
Section: Characteristics Of Studies Included In the Reviewmentioning
confidence: 99%
“…This incentive was found to be a cost-effective way of increasing facility delivery in rural Zambia. 55…”
Section: Journal Of Global Health Reportsmentioning
confidence: 99%